X-Ray Diffraction of Cobalt(II) Complex of S4N3Cl - Upadhyay, Shalini; Jadon, S.P.S. (Asian Journal of Chemistry, 2016)
On the basis of mass, IR and XRD spectra, the complex of S4N3Cl with Co(CH3COO)2·4H2O is found to be a hexadentate coordinated complex, having triclinic geometrical array.